Some Solutions to improve cultural and spiritual life of university students today - Nguyễn Thị Hiếu (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
Along with the task of economic development, which is inevitably the task of building culture, the work of building spiritual cultural life becomes an urgent task in the face of a rapidly changing world like today. In the national education system, university level is a very important level of education in order to create human resources for society. College students are a special age, with strong changes, development, and changes both physically, psychologically and cognitively, intellectually, spiritually and emotionally… The cultural and spiritual life of students plays a particularly important role, contributing to the formation of the personality and bravery of future generations of citizens. Within the scope of this article, the author focuses on "some solutions to improve the cultural and spiritual life of university students today".